Environment - Raven, Peter H.; Berg, Linda Ruth , 1947-; Hassenzahl, David M. (John Wiley & Sons, 2013)
Theeight edition of Environment builds on the previous comprehensive, systems-based environmental science issue with more in-depth information on systems approach, which emphasizes the interconnected nature of environmental science throughout the text